Pengaruh Penerapan Aplikasi Rencana Kegiatan Dan Anggaran Sekolah (Arkas) Dan Kompetensi Sumber Daya Manusia Terhadap Akuntabilitas Pengelolaan Dana Bos Di Moderasi Oleh Komitmen Pimpinan Di Sma Kabupaten Serdang Bedagai - Sitohang, Sasmitha; Sari, Eka Nurmala; Irfan, Irfan (CV. ITTC INDONESIA, 2024)
This study aims to analyze the influence of human resource (HR) competence and the Regional Government Information The management of the BOS fund program has several factors to achieve success, including a professional, reliable management team (HR) who upholds the principles of accountability and transparency. The purpose of this study was to test and analyze the effect of the implementation of the School Activity and Budget Plan Application (ARKAS) and Human Resources (HR) competence on the accountability of BOS fund management in Senior High Schools in Serdang Bedagai Regency. To test and analyze the commitment of the leadership to moderate the effect of the School Activity and Budget Plan Application (ARKAS) and Human Resources (HR) competence on the accountability of BOS fund management in Senior High Schools in Serdang Bedagai Regency. The research approach uses quantitative associative. In this study, the research instrument used was a questionnaire. This study uses the Structural Equation Modeling (SEM) analysis method using SmartPLS.3 software which is run on a computer media. Based on the results of the study, there is an effect of the implementation of ARKAS on the accountability of BOS fund management. There is an effect of HR competence on the accountability of BOS fund management. Leadership commitment can moderate the effect of the implementation of ARKAS on the accountability of BOS fund management. Leadership commitment can moderate the influence of HR competency on BOS fund management accountability.